Pentagamaboronon-0 increased cytotoxicity of and inhibited metastasis induction by doxorubicin in breast cancer cells - Ratih Kusumastuti, Rohmad Yudi Utomo, Annisa Khumaira, Herwandhani Putri, Riris Istighfari Jenie, Edy Meiyanto (Journal of Applied Pharmaceutical Science, 2019)
Long-term use of doxorubicin (DOX) causes several side effects, especially induction of metastasis, in breast cancer cells. Pentagamaboronon-0 (PGB-0) or 2,5-bis(4-boronic acid benzylidene) cyclopentanone is a novel curcumin analog that exerts cytotoxic effects on Human Epidermal Growth Factor Receptor 2 (HER2)-positive breast cancer cells. The objective of this study was to evaluate PGB-0 as a co-chemotherapeutic agent on DOX-induced metastatic breast cancer cells, 4T1. Potential cytotoxic and antimetastatic activities of PGB-0 were screened by molecular docking under PLANTS software, which revealed that the PGB-0 interacted with matrix metalloproteinase-9 (MMP-9) and Inhibitor Kappa β Kinase (IKKβ). 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay showed that PGB-0 and DOX exhibited cytotoxic effects on 4T1 breast cancer cells, with IC50 values of 294 and 2.4 μM, respectively, and synergistically increased the cytotoxicity of DOX. Results of propidium iodide staining flow cytometry revealed that the PGB-0 and its combination with DOX induced cell cycle arrest in the S phase and the G2/M phase, respectively. In addition, PGB-0 and its combination with DOX induced apoptosis. Regarding the antimetastatic activity, a single treatment with PGB-0 inhibited cell migration, while its combination with DOX inhibited cell migration with more potency than that with single treatment, as assessed through wound healing assay. Gelatin zymography revealed that the PGB-0 and its combination with DOX inhibited MMP-9 activity. Immunoblotting assay showed that the PGB-0 and its combination with DOX decreased the expression of Rac1 and p120. In conclusion, PGB-0 increased the cytotoxicity and inhibited the induction of metastasis by DOX in breast cancer cells.
Keywords: PGB-0, co-chemotherapy, cell cycle, MMP-9, metastasis.